Synthesis of NiO–Ce0.9Gd0.1O1.95 nanocomposite powders for low-temperature solid oxide fuel cell anodes by co-precipitation - Ding, Changsheng; Lin, Hongfei; Sato, Kazuhisa; Hashida, Toshiyuki (Scripta materialia, 2009)
Homogenous NiO-Ce0.9Gd0.1O1.95 (GDC) nanocomposite powders were successfully synthesized by a hydroxide co-precipitation method. The synthesized powders consist of NiO and GDC double phases, and the average particle size is in the range of 10-40 nm. A solid oxide fuel cell (SOFC) with anode prepared from the synthesized NiO-GDC nanocomposite powders shows high electrical performance at low operating temperatures. Results indicate that the synthesized NiO-GDC nanocomposite powders are suitable anode materials for low-temperature SOFCs.